1993
DOI: 10.1038/bjc.1993.224
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of doxorubicin toxicity to multidrug and intrinsically drug resistant cell lines by anti-oestrogens and their major metabolites

Abstract: Summary The ability of the anti-oestrogens tamoxifen, toremifene and their 4-hydroxy and N-desmethyl metabolites to modify doxorubicin (dox) toxicity to intrinsically resistant and multidrug resistant cell lines was compared, using human breast and lung cancer, and Chinese hamster ovary cell lines. The anti-oestrogens significantly enhanced dox toxicity to multidrug resistant, P-glycoprotein-positive cell lines, but did not affect toxicity to intrinsically resistant, P-glycoprotein-negative cells. Modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 28 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Although it has been proposed that this chemosensitizing activity of TAM may be due to an inhibition of P-glycoprotein function (Kirk et al, 1993;Leonessa et al, 1994), our group (De Vincenzo et al, 1996) and others (Kang et al, 1993) previously failed to demonstrate this interaction in multidrug resistant (MDR)-bearing human cancer cells. Moreover, TAM potentiates the anti-tumour effects of taxanes also in MDR-negative cancer cell lines (Ferlini et al, 1997).…”
Section: Discussionmentioning
confidence: 84%
“…Although it has been proposed that this chemosensitizing activity of TAM may be due to an inhibition of P-glycoprotein function (Kirk et al, 1993;Leonessa et al, 1994), our group (De Vincenzo et al, 1996) and others (Kang et al, 1993) previously failed to demonstrate this interaction in multidrug resistant (MDR)-bearing human cancer cells. Moreover, TAM potentiates the anti-tumour effects of taxanes also in MDR-negative cancer cell lines (Ferlini et al, 1997).…”
Section: Discussionmentioning
confidence: 84%
“…Tamoxifen has been reported to reverse multidrug resistance in P-glycoprotein-expressing cell lines (10)(11)(12)(13), and tamoxifen binds to P-glycoprotein (Callaghan, R., and C. F. Higgins, manuscript submitted for publication). P-glycoprotein is a 170-kD polypeptide that confers multidrug resistance by pumping hydrophobic compounds out of cells, reducing their intracellular concentrations and, hence, toxicity ( 14).…”
Section: Introductionmentioning
confidence: 99%
“…Ramu et al (1984) suggested that the reversal of the doxorubicin-acquired resistance by the triparanol analogues is unrelated to estrogenic or antiestrogenic activities. Kirk et al (1993) also suggested that modification of doxorubicin toxicity by anti-estrogens occurred irrespective of ER status and was unaffected by estradiol, indicating that enhanced doxorubicin toxicity is not an anti-estrogenic effect. Although we were unable to demonstrate the presence of ER in EATC, tamoxifen treatment caused the cells to accumulate in G1-G0 and decreased the TLI.…”
Section: Discussionmentioning
confidence: 99%